You're a good sport, Charlie Brown - Mendelson, Lee.; Melendez, Bill.; Schulz, Charles M. (Charles Monroe), 1922-2000.; Roman, Phil, 1930-; Guaraldi, Vince; Charles M. Schulz Creative Associates; United Feature Syndicate; Warner Home Video (Firm) (Burbank, Calif. : Warner Home Video, 2009)
It's Motocross season, and competing against Peppermint Patty and the Masked Marvel (a.k.a. Snoopy), can intimidate anyone. But if Charlie Brown, unlucky number 13, can keep the pace slow and steady, he might just win the race. It's fast and furious right up to the finish line.
Title from container.
Full screen.
Originally broadcast on television in 1975.
Special features: Another story featuring the gang: "You're the greatest, Charlie Brown;" all-new featurette "Dust yourself off and pick yourself up, Charlie Brown."
Original score composed and performed by Vince Guaraldi.
Not rated.
Keywords: Brown, Charlie -- (Fictitious character) -- Juvenile films; Snoopy -- (Fictitious character) -- Juvenile films; Motocross -- Juvenile films; Motorsports -- Juvenile films; Motorcycles, Racing -- Juvenile films; Animated films; Children's films; Comedy films; Films for the hearing impaired